Friedrich Pollock The Éminence Grise of the Frankfurt School - Lenhard, Philipp 1980- (BRILL, 2024)
Philipp Lenhard's book is the first biography on Friedrich Pollock (1894-1970). It portrays the life of a man who played a defining role in the Frankfurt School of Critical Theory but always stayed in the background.
Description based on publisher supplied metadata and other sources
Keywords: Pollock, Friedrich / 1894-1970; Social scientists / Germany / Biography; Economists / Germany / Biography; Sociologists / Germany / Biography; Philosophers / Germany / Biography; Jews / Germany / Biography